Source-Aware Redundant Packet Forwarding Scheme for Emergency Information Delivery in Chain-Typed Multihop Wireless Sensor Networks. (31st March 2015) - Zhou, Gongbo; Zhu, Zhencai; Zhang, Peng; Li, Wei
Abstract : For emergency information delivery of chain-typed multihop wireless sensor networks in closed long tunnel (CWSN-C), the scheme of sending the same packet multiple times is a good choice. In this paper, taking the application of rigid sliding guide obliquity monitoring in deep shaft as background, the source-aware redundant packet forwarding scheme for emergency information delivery in CWSN-C (SRPFEC) is proposed firstly. Secondly, more of comprehensive factors including application QoS and energy efficiency are considered for determining the number of redundant packets. Then, a method of solving for the number of redundant packets is proposed. Finally, Monte Carlo method and network simulation are employed to study the performances of proposed SRPFEC. The results show that (1) non-ACK scheme is highly suitable for the condition of large network size and hazardous wireless communication environment; (2) the non-source-aware solution is easy to use and is suitable for the occasion where the node could be replaced on demand expediently; (3) the source-aware solution has the better performance in energy efficiency and is suitable for the occasion where the network lifetime needs to be determined before deployment, and the node could not be replaced easily.